Science Literacy and Critical Thinking Skills of Elementary School Students: A Correlation Study - Ayu Apriliana, Nindi; Anggrella, Dita Purwinda (UIN Raden Mas Said Surakarta, 2024)
Scientific literacy includes students' ability to understand scientific concepts, apply that knowledge to solve problems and make decisions based on scientific information. Meanwhile, critical thinking skills involve analysing, evaluating, and synthesising information logically. This study aims to analyse scientific literacy skills, critical thinking skills, and the relationship between the two in elementary school students. The research method used is a quantitative approach with a correlational type. The population in the study involved 68 students of grade V MI Muhammadiyah Trangsan, so a sample of 58 students was obtained using the Slovin formula. The sampling technique used was simple random sampling. Data were collected through essay tests of scientific literacy and critical thinking skills on the water cycle material. The results showed an average value of scientific literacy of 62.71, which is in the moderate category; an average value of critical thinking skills of 71.93, which is in the moderate category; and a correlation coefficient value of 0.617, which indicates a fairly strong positive relationship. This result means that the higher the students' scientific literacy skills, the better their critical thinking skills. A simple linear regression test shows R2 = 0.381, meaning that scientific literacy factors influence 33.8% of critical thinking skills, while other factors influence the remaining 66.2%. This finding indicates the importance of strengthening scientific literacy in learning to improve students' critical thinking skills.